Exploring repeating students’ feelings and attitudes towards learning ESL writing - Sheikh Ahmad, Ismail; Kassim, Rosnani; Zubairi, Ainol Madziah (IIUM Press, 2017)
In ESL writing classes or courses, we often observe students struggling to learn the writing skills. Some students even fail the same writing course repeatedly. Failing and repeating the same writing course will certainly affect the repeaters in several aspects. Hence, this study sought to explore the feelings and attitudes of these students who were repeaters in learning writing in a pre-sessional English course at the International Islamic University Malaysia (IIUM). Based on semi-structured interviews with the repeaters and their writing instructors, it was revealed that the repeaters had some negative feelings and attitudes, namely feeling uncertain with one’s own ability, lacking motivation, suffering from anxiety and having poor relationship with their teachers. This paper further discussed these negative feelings and attitudes in light of scholarly thoughts of past and contemporary Muslim scholars to shed some light on aspects that are essential in ensuring successful language learning for repeating student, particularly in relation to their feelings and attitudes towards learning English writing skills. This study has major significance especially in enabling writing instructors to understand the repeaters better and to help them develop positive attitudes towards learning writing in English. The pedagogical implications and recommendations are also discussed